Knoevenagel Condensation Reaction Using Brønsted-Acidic Ionic Liquids as Green and Reusable Catalysts - Tavakoli-Hoseini, N.; Heravi, M.M.; Bamoharram, F.F. (Asian Journal of Chemistry, 2010)
Knoevenagel condensation reaction of aromatic aldehydes with malononitrile proceeded efficiently in water using Brønsted-acidic ionic liquids as catalyst. The experimental results show that these ionic liquids have good catalytic activities to the Knoevenagel condensation. The reactions are carried out in a few minutes with high yields. The products could simply be separated from the catalyst/water and the catalyst could be recycled without noticeably decreasing the catalytic activity.